Inclusion of the Child Friendly School Concept into Formal Teacher Education in Bhutan - Dorj, Rinchen (THE PRIMARY TEACHER, 2009)
Perched in the heart of the Himalayas, the Kingdom of Bhutan has a unique history of development of a formal education system. In the early 1960s, Bhutan opened its doors to the rest of the world and the forces of change and modernisation. Since the start of the First Five Year Plan in 1961 remarkable progress has been made in the field of education. Access to basic education is now the right of all Bhutanese and it is the key to most of the nation’s development objectives. The government aspires to develop an education system which provides access to a free (at least at the primary level) and a wholesome education for all children. Formal education in Bhutan consists of six years of primary education (including one year preprimary), two years of lower secondary and two years of middle secondary education, two years of higher secondary and three years of college education. The official age for children to attend formal schooling (preprimary) is 6 years. However, education even at the primary level is not yet completely free, neither is it compulsory